2022
DOI: 10.1038/s41598-022-10906-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward passive BCI: asynchronous decoding of neural responses to direction- and angle-specific perturbations during a simulated cockpit scenario

Abstract: Neuroimaging studies have provided proof that loss of balance evokes specific neural transient wave complexes in electroencephalography (EEG), called perturbation evoked potentials (PEPs). Online decoding of balance perturbations from ongoing EEG signals can establish the possibility of implementing passive brain-computer interfaces (pBCIs) as a part of aviation/driving assistant systems. In this study, we investigated the feasibility of identifying the existence and expression of perturbations in four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Extr. 2024, 6 200 have voluntary control over it, also called passive brain-computer interface (BCI), using electroencephalography (EEG) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Extr. 2024, 6 200 have voluntary control over it, also called passive brain-computer interface (BCI), using electroencephalography (EEG) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no differences were found in the N1 peak amplitude and latency as a function of the perturbation direction. In our previous study [24], it was shown that the modulation of cortical responses elicited by balance perturbation carries directionand angle-specific information which can be classified with reliable accuracy. In another study by Adkin and colleagues [22], they applied displacement in predictable and unpredictable manners.…”
Section: Introductionmentioning
confidence: 99%
“…In many modern applications, such as manufacturing robots 1 , 2 , bionic robots 3 , 4 , medical robots 5 , 6 and aeronautical robots 7 , 8 , the mechanism is subject to external payloads and gravity of its own components which in turn induce deformations causing positioning errors. In order to improve motion accuracy and machining accuracy, stiffness analysis becomes an important solution.…”
Section: Introductionmentioning
confidence: 99%